STRATEGI PEMASARAN PRODUK HERBALIFE (STUDI KASUS RUMAH NUTRISI GREEN) - Gleyni ., Supit; Ribka M. Kumaat; Agnes E. Loho (AGRI-SOSIOEKONOMI, 2016)
This study aims to determine the marketing strategy Herbalife in Manado City. The method of determining the area of research done in purposive, using the case study method which is a description of a real-life experience, which is used to make points, raise issues or otherwise enhance understanding and learning experience of the participants. Where, Nutrition Green House as a location or point of research. Data analysis method used is descriptive analysis, SWOT analysis, and business strategy theory. The results showed that the strategies that have been applied are maintained and add to the marketing strategy of "investment strategy", which prioritizes the development of this strategy over the larger business. Home Nutrition Green brings their positive impact on the communities that exist around the city of Manado. Its positive impact, among other things, the public can find out how to live healthy by consuming Herbalife products with the benefits contained in any product without considering the price of Herbalife products.